Immune-Related Adverse Events: A Case-Based Approach - Connolly, Caoilfhionn; Bambhania, Kalindi; Naidoo, Jarushka (Frontiers in Oncology, 2019)
Immunotherapy has heralded the advent of a new era in oncology. Immune checkpoint inhibitors (ICIs) enhance anti-tumor immunity, thereby reinvigorating a patient’s immune system to fight cancer. While therapy with this class of agents has resulted in improved clinical outcomes for patients with multiple tumor types, a broad spectrum of immune-related adverse events (irAEs) may affect any organ system, with variable clinical presentations. Prompt recognition and management of irAEs are associated with improved irAE outcomes, and represents an important new clinical challenge for practicing oncologists. Herein, we provide a comprehensive case-based review of the most common and clinically-important irAEs, focussing on epidemiology, clinical manifestations, and management. We also examine future strategies that may provide meaningful insights into the prevention and management of irAEs.